Troubleshooting & fixing common problems in PCs & laptops : a quick illustrative guide to troubleshoot repair, upgrade, and optimize your computer system - Lee, Gilbert (Canada : Churchgate Publishing House, 2021)
The book is carefully compiled in friendly tones with good numbers illustrations to expose how you can easily troubleshoot and fix common problems in laptops and PCs.
Section 1. Common Problems in Laptops -- Section 2. Common Problem in PC's -- Section 3. Software issues in Laptops and PCs -- Section 4. How to Repair a Hard Drive.
Keywords: COMPUTER SOFTWARE